2020
DOI: 10.1007/s42452-020-2190-9
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride nanoplatelets incorporated titania based type-II heterostructure and its enhanced performance in photoelectrocatalytic water splitting

Abstract: In this present work, the synthesis of g-C 3 N 4 /TiO 2 nanocomposites with different wt.% g-C 3 N 4 to form a type-II heterostructure and its potential application towards photoelectrocatalytic water splitting was discussed. The synthesized g-C 3 N 4 nanoplatelets incorporated TiO 2 nanocomposites were characterized by various analytical techniques such as UV-vis diffuse reflectance spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, photoluminescence spectroscopy, X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Several carbon-based materials such as graphene oxide (GO), carbon nanofibers (CNFs), carbon nanotubes (CNTs), ordered mesoporous carbon (OMC), and graphitic carbon nitride (GCN) have been used for electrochemical sensors. Among them, GCN received a lot of attention due to its unique structural characteristics, large surface area, high electrical conductivity, high mechanical strength, and chemical stability. In addition, many researchers have reported that heteroatom (S, N, P) doping in the GCN framework is an excellent strategy for improving its activity more effectively for various electrochemical applications, including sensing, photocatalytic degradation, and water catalysis. Through this, MoN’s stability and electrical conductivity can be enhanced by forming a composite material with heteroatom-doped GCN. As a result, the combination of MoN and heteroatom-doped GCN is expected to significantly enhance the activity of the electrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Several carbon-based materials such as graphene oxide (GO), carbon nanofibers (CNFs), carbon nanotubes (CNTs), ordered mesoporous carbon (OMC), and graphitic carbon nitride (GCN) have been used for electrochemical sensors. Among them, GCN received a lot of attention due to its unique structural characteristics, large surface area, high electrical conductivity, high mechanical strength, and chemical stability. In addition, many researchers have reported that heteroatom (S, N, P) doping in the GCN framework is an excellent strategy for improving its activity more effectively for various electrochemical applications, including sensing, photocatalytic degradation, and water catalysis. Through this, MoN’s stability and electrical conductivity can be enhanced by forming a composite material with heteroatom-doped GCN. As a result, the combination of MoN and heteroatom-doped GCN is expected to significantly enhance the activity of the electrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%
“…It may be due to the synergistic effect between g-C 3 N 4 and (101)-(001)-TiO 2 causing a change in the spatial structure, which in turn causes a red shift. 47 …”
Section: Resultsmentioning
confidence: 99%
“…It may be due to the synergistic effect between g-C 3 N 4 and ( 101)-(001)-TiO 2 causing a change in the spatial structure, which in turn causes a red shi. 47 Another reason may be the rearrangement of energy levels caused by the formation of chemical bonds (such as Ti-O-C and C-O-C covalent bond) between g-C 3 N 4 and ( 101)-(001)-TiO 2 , resulting in the redshi of the absorption-band edge. 48 Combining the UV-Vis DRS results with the above characterization results clearly indicates that the formation of the composites may be due to chemical bonding between the g-C 3 N 4 and ( 101)-(001)-TiO 2 interfaces rather than a physical mixture of g-C 3 N 4 /(101)-( 001)-TiO 2 .…”
Section: Uv-vis Drs Analysismentioning
confidence: 99%
“…Herein, the mentioned position of VB and condition band of MFO and SCNNS was calculated by applying the following empirical equations. [ 139,140 ] EVBgoodbreak=normalχgoodbreak−Eegoodbreak+0.50.25em()normalEnormalg ECBgoodbreak=EVBgoodbreak−Eg Here, the terms E VB and E CB represent the VB and CB potential, respectively. Additionally, E g depicts the band gap energy value of semiconductor and E e is the energy of the free electrons versus hydrogen (4.5 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the mentioned position of VB and condition band of MFO and SCNNS was calculated by applying the following empirical equations. [139,140]…”
Section: Photocatalytic Degradation Mechanismmentioning
confidence: 99%